THE EFFECT OF TOMAN FISH EXTRACT (Channa Micropeltes) ONNEUTROPHILIN DIABETES MELLITUSWOUND HEALING (In Vivo Study in the Back of Male Wistar Mice (Ratus Novergicus) - Fajriani, Nuril; Nindia Carabelly, Amy; Laillyza Apriasari, Maharani (FKG Unlam, 2018)
Background: Toman fishcontains albumin and unsaturated fatty acids which can be an alternative of diabetes mellitus wounds healing process. People with diabetes mellitus have their neutrophil decreased. Albumin increases the number of neutrophil. Unsaturated fatty acid decreases the number of neutrophil. Purpose: To prove the effect of toman fish extract of 16 ml/Kg BW mice orally on thenumber of neutrophil in day 2, 4, and 8 of male wistarmice with diabetic wound. Materials and Method: This research applied pure experimental research method with posttest only control design. This research took 36 wistarmice which weredivided into negative control group which is given BR2 feed, treatment group which is giventoman fish extract in 16 mL/Kg BW mice and positive control group which is given haruan fish extract in 13.54 mL/Kg BW mice. The Result: One-way ANOVAshowedthat there wassignificant differenceof all groups in day 2 (p=0.000), day 4 (p=0.000) and day 8 (p=0.000). Post-Hoc LSD test for the average of neutrophil number showedthat there was significant difference (p<0.05) between the negative control group, treatment group and the positive control group. Conclusion: Toman fish extract has an effect which increasesthe number ofneutrophil in day 2 and decreasesthe number of neutrophil in day 4 and 8 on the healing of diabetic wound in mice.